Laurentian crust in northeast Australia: Implications for the assembly of the supercontinent Nuna - Nordsvan, A.; Collins, W.; Li, Z.; Spencer, Christopher; Pourteau, Amaury; Withnall, I.; Betts, P.; Volante, S. (Geological Society of America, 2018)
The Georgetown Inlier of northeast Australia provides evidence of critical links between Australia and Laurentia during the late Paleoproterozoic and the early Mesoproterozoic. Detrital zircon age spectra from sedimentary strata within the inlier show two distinct changes in sedimentary provenance: (1) the lowermost units (depositional age ca. 1700–1650 Ma) have detrital zircon age spectra that strongly resemble Laurentian magmatic ages and detrital zircon age spectra of the similar-aged Wernecke Supergroup of northwest Laurentia; (2) sediments deposited from ca. 1650 to 1610 Ma show a unimodal proximal signature; and (3) postorogenic sediments deposited after 1550 Ma have detrital zircon age spectra like the Mount Isa Inlier of the North Australia craton. Along with new paleocurrent measurements, the detrital age data challenge current models that suggest that the Georgetown Inlier was part of Australia before ca. 1700 Ma. Rather, we argue it was a continental ribbon rifted from west Laurentia during slab rollback ca. 1680 Ma; by 1650 Ma, the Georgetown Inlier had completely separated from Laurentia, and ca. 1600 Ma collided with Australia during supercontinent Nuna amalgamation.